2014
DOI: 10.1111/jdi.12239
|View full text |Cite
|
Sign up to set email alerts
|

Relationship and factors responsible for regulating fasting and post‐challenge plasma glucose levels in the early stage development of type 2 diabetes mellitus

Abstract: Aims/IntroductionElevation of 2-h plasma glucose (2-h PG) levels keeps step with fasting plasma glucose (FPG) levels elevation, but some individuals show dominant elevation of 2-h PG and others FPG. We analyzed dependent and independent relationships between 2-h PG and FPG, and investigated the factors regulating 2-h PG and FPG.Materials and MethodsIn 1,657 Japanese participants who underwent a 75-g oral glucose tolerance test at the initial examination for a medical check-up, we carried out simple linear regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Fearch et al concluded that a progressive and age-dependent loss of insulin secretion was involved in the development of postchallenge hyperglycemia in relation to progression from NGT to isolated IGT by 5-year follow-up study [ 28 ]. There are additional studies that reported that the main factors responsible for elevation of 2 h PG levels were decreased early-phase insulin secretion linked to aging [ 8 , 29 31 ]. IGT subjects showed a larger decrease in insulin secretion compared with NGT subjects and early-phase was decreasing more than second-phase of insulin secretion [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fearch et al concluded that a progressive and age-dependent loss of insulin secretion was involved in the development of postchallenge hyperglycemia in relation to progression from NGT to isolated IGT by 5-year follow-up study [ 28 ]. There are additional studies that reported that the main factors responsible for elevation of 2 h PG levels were decreased early-phase insulin secretion linked to aging [ 8 , 29 31 ]. IGT subjects showed a larger decrease in insulin secretion compared with NGT subjects and early-phase was decreasing more than second-phase of insulin secretion [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Homeostatic model assessment of β-cell function (HOMA-β) was from this equation: 20 ×INS 0 (IU/L)/(G 0 (mmol/L)-3.5) [ 6 ]. Insulin sensitivity was evaluated by insulin sensitivity index (ISI) composite: 10,000/([G 0 × INS 0 ] × [mean G 0-120 × mean INS 0-120 ] (mean G 0-120 refers to the average plasma glucose level for the first 120 minutes calculated by the average value of G 0 , G 30 , G 60 and G 120 ) [ 28 ]. Early insulin secretion was calculated based on the formula for insulinogenic index (IGI, ΔINS 30 /ΔG 30 ): (INS 30 -INS 0 ) (IU/L)/(G 30 -G 0 ) (mmol/L) [ 29 ].…”
Section: Methodsmentioning
confidence: 99%